Isolasi dan Pemurnian Protein dari Lembaga Jagung (Corn Germ) Menggunakan Metode Presipitasi dan Dialisis: Protein Isolation and Purification from Corn Germ Using Precipitation and Dialysis Methods - Nancy Siti Djenar; Joko Suryadi (KOVALEN: Jurnal Riset Kimia, 2022)
The protein contained in corn germ can be used as a raw material that has the potential to provide many benefits in the food, pharmaceutical, and plastic industries. Corn germ with the highest content of protein is around 12-18.4%. In this study, protein from corn germ was isolated and homogenized using tris buffer HCl at pH 7.2. To obtain the protein fraction, precipitation was carried out (salting-out) using a solution of (NH4)2SO4 with saturation levels of 25%, 50%, and 70% respectively. The purification process was carried out by dialysis for 24 hours. The dialysis produced pure protein with a concentration of 4.161%. Based on the identification of functional groups using an FT-IR spectrophotometer, it was shown that the isolated and purified corn germ protein contained four absorption bands, including amide A (3211.48 cm-1 and 3226.91 cm-1), amide I (1633 cm-1 and 1629.85 cm-1), amide II (1527 cm-1 and 1552.70 cm-1) and amide III (1296.16 cm-1). The four absorption bands correspond to the wavenumbers of corn protein stated in the literature and are estimated to contain albumin, globulin, glutelin, and zein.